INFLUENCE OF POLYMORPHIC VARIANT C-108T OF PON1 GENE ON THE RISK OF DEVELOPING HYPERTENSION OR BREAST CANCER IN WOMEN FROM UKRAINE - Fishchuk, L.E.; Gorovenko, N.G. (World of Medicine and Biology, 2013)
The results determination of polymorphic variant C-108T of PON1 gene in 131 women with breast cancer (BC), 131 women with hypertension and in 102 healthy women (control group). It was show that polymorphic variant C-108T of PON1 gene affects on the risk of developing breast cancer and hypertension in women from Ukraine, including: 1) the presence of T-108 allele increasing risk of hypertension more than in 3 times in women after 54 years, 2) the presence of C-108C genotype reducing the risk of breast cancer almost in 3 times in women after 54 years, on the contrary, the presence of C-108T genotype increasing risk of developing breast cancer in 3 times.
Keywords: PON1; gene polymorphism; breast cancer; hypertension